2022
DOI: 10.1038/s41556-022-01037-0
|View full text |Cite|
|
Sign up to set email alerts
|

Multivalent interactions facilitate motor-dependent protein accumulation at growing microtubule plus-ends

Abstract: Growing microtubule ends organize end-tracking proteins into comets of mixed composition. Here using a reconstituted fission yeast system consisting of end-binding protein Mal3, kinesin Tea2 and cargo Tip1, we found that these proteins can be driven into liquid-phase droplets both in solution and at microtubule ends under crowding conditions. In the absence of crowding agents, cryo-electron tomography revealed that motor-dependent comets consist of disordered networks where multivalent interactions may facilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
4
13
0
Order By: Relevance
“…We find that the purified IDR protein readily undergoes LLPS at physiological salt conditions, in the absence of crowding agents, and near the estimated KIF1C endogenous concentration. This is in contrast to other MAPs that accumulate at microtubule plus ends, such as EB1 and CLIP-170, which undergo LLPS at mM concentrations or in the presence of crowding agents 68,68,92,93 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We find that the purified IDR protein readily undergoes LLPS at physiological salt conditions, in the absence of crowding agents, and near the estimated KIF1C endogenous concentration. This is in contrast to other MAPs that accumulate at microtubule plus ends, such as EB1 and CLIP-170, which undergo LLPS at mM concentrations or in the presence of crowding agents 68,68,92,93 .…”
Section: Discussionmentioning
confidence: 58%
“…A KIF1Bα stalk+tail construct, KIF1Bα(ST), forms small puncta when expressed in hTERT-RPE cells but forms a network-like structure when expressed in COS-7 cells (Fig S8 A), suggesting that KIF1Bα may also be capable of LLPS. However, KIF1Bα puncta do not associate with RNA-containing P-bodies and stress granules ( Microtubules have emerged as a platform for LLPS 69 as several non-motor microtubuleassociated proteins (MAPs) can undergo LLPS, including tau, EB1, CLIP-170, BuGZ, TPX2, and CAMSAP2, and thereby regulate microtubule nucleation, branching, bundling, and/or mitotic spindle formation [64][65][66][67][68][70][71][72][90][91][92][93] . However, KIF1C condensates appear to be distinct from these other microtubule-associated biomolecular condensates.…”
Section: Llps Of Kinesins and Other Microtubule-associated Proteinsmentioning
confidence: 99%
“…Protein condensation mediated by liquid-liquid phase separation (LLPS) has emerged as a mechanism for locally concentrating components to drive biochemical interactions and chemistry in cells [10][11][12][13][14] . Although these droplet structures bear little resemblance to the highly ordered structures of the cytoskeleton described above, recent studies have suggested roles for phase separation in amplifying the activity of large MAPs associated with bundling, branching, and tip growth such as tau, TPX2, NuMA, and +TIPs [14][15][16][17][18][19] . These observations are intriguing, as the high concentrations and reduced-order of liquid condensates in principle could provide both the valency and flexibility needed to couple interacting microtubules across a range of geometries.…”
Section: Introductionmentioning
confidence: 95%
“…These observations are intriguing, as the high concentrations and reduced-order of liquid condensates in principle could provide both the valency and flexibility needed to couple interacting microtubules across a range of geometries. However, direct evidence for this interpretation is complicated by the fact that these MAPs (1) normally contain multiple MT-binding regions [20][21][22] , (2) may need extra molecular crowders or cytoplasmic extracts to drive their microtubule-directed activity 15,16,23 , and (3) often recruit other client proteins to further coordinate MT-crosslinking 17,24,25 . As a result, the specific mechanisms and biophysical principles by which protein condensates directly contribute to the emergent microtubule architectures these MAPs produce is often unclear and their functional relevance and regulation in vivo remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Multivalent interactions play even bigger roles at the microtubule tips where many EB-dimers form interactions with multiple partners 45,46 . Tails of EB dimers form interactions with the cargo binding domains of dimeric HSET.…”
Section: Introductionmentioning
confidence: 99%